Investigation of benfotiamine's protective effects on liver tissue in experimental carbon tetrachloride induced liver injury - Karakaya, Bulent; Kuloglu, Tuncay; Onalan, Erhan; Tektemur, Nalan Kaya; Donder, Emir (Cukurova Univ, Fac Medicine, 2020)
Purpose: In this study, we aimed to investigate the protective effects of benfotiamine on experimental liver injury caused by carbon tetrachloride (CCl4). Materials and Methods: In this study, 30 male Wistar albino rats were used. Rats were equally divided into 5 groups. No application was made to control group. The CCl4 group was injected i.p with1ml/kg CCl4:olive oil (1:2) mixture on the 1st and 8th days, and the CCl4+benfotiamine group was treated i.p with 1 ml/kg CCl4: olive oil (1: 2) mixture twice on the 1st and 8th days and orally with 70 mg/kg/day benfotiamine. To the benfotiamine group, 70 mg/kg/day benfotiamine was given orally for 14 days. To the olive oil group, 2 ml/kg olive oil was given i.p. on 1st and 8th days. Finally, rats were decapitated. Liver tissues were removed and paraffin blocks were prepared. Tissues were stored at -80 oC for malonaldeyhde (MDA) assay. Results: There were no significant differences between the control, benfotiamine and olive oil groups. Compared with the control group, there was a significant increase in MDA, apoptosis and bax immunoreactivity in CCl4 group. Compared with the CCl4 group, there was a significant decrease in MDA, apoptosis and bax immunoreactivity in the CCl4+benfotiamine group. Conclusion: CCl4 increases MDA, apoptosis and bax immunoreactivity, and benfotiamine, given as treatment, reduces these parameters.
Keywords: Rat; carbon tetrachloride; benfotiamine; apoptosis